Health Issues in The WTO Dispute Concerning Importation of Chicken Meat and Products between Indonesia and Brazil - Ari Siswanto (University of Udayana, 2020)
Article XX(b) of GATT justifies countries to adopt and apply trade measures to protect human health. It means that as long as the elements specified in Article XX(b) are satisfied, certain trade measures which infringe GATT rules and principles are permitted. Unfortunately, the rise of new protectionism and the unclear meaning of elements contained in Article XX(b) has likely attracted countries to use Article XX(b) as a pretext for enforcing protectionist trade measures. This research aims to address the meaning of elements of